The effects of carbohydrate supplementation on the GH/IGF-1 axis, cortisol, insulin, and glucose in adult runners - Bretas Oliveira, Alexandre; Santa Capita Cerqueira, Henrique; Paixão Dos Santos Magraner, José Maurício; Custódio, Rodrigo Jóse; Martinelli Jr., Carlos Eduardo; Tourinho Filho, Hugo (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Purpose. Hormones are largely responsible for the integrated communication of various physiological systems that modulate cell growth and development. However, specific hormonal influences must be considered in the context of the entire endocrine system and their relationship with other physiological systems. The serum concentrations of these hormones can directly affect athlete performance and reflect training status during preparation.Methods. Concentrations of growth hormone (GH), insulin-like growth factor-I (IGF-1), cortisol, insulin, and glucose were measured at rest 30 min before a simulated race and 30 min after race completion. Student’s t-test for paired samples analysed normally distributed data, while Wilcoxon’s non-parametric test assessed other variables. A significance level of p 0.05 was adopted.Results. GH and cortisol serum concentrations increased after running, with (GH: p = 0.03; cortisol: p = 0.001) and without (GH: p = 0.001; cortisol: p = 0.004) carbohydrate supplementation. Glucose concentrations only increased at the end of the race with carbohydrate supplementation (p = 0.01) but remained unchanged after the race without supplementation. Insulin concentrations rose at the end of the race with carbohydrate supplementation (p = 0.05) and lowered without supplementation (p = 0.03). IGF-1 levels did not change with or without carbohydrate supplementation.Conclusions. Changes in serum GH, cortisol, and insulin during the race appeared to contribute to serum IGF-1 and glucose concentration maintenance and runner performance.
Keywords: endurance; glucose; aerobic exercise; running performance; biomarkers